Genetic influences on predicted methane production and natural resource allocation of beef cattle in the Great Plains - Lakamp, Andrew David (Kansas State University, 2021)
The environmental impact of the beef industry has recently become an area of increasing scientific investigation. One of the objectives of this thesis was to examine how genetic selection and breeding could influence the environmental sustainability of the beef sector by estimating genetic variance parameters and discovering loci associated with predicted methane traits. Observed feed intake of 830 crossbred steers was used to calculate predicted methane traits via three enteric methane estimation equations from Ellis et al. (2007), Mills et al. (2001), and IPCC (2019). Variance components were estimated using genomic best linear unbiased prediction (GBLUP). Heritabilities for each predicted methane trait ranged from 0.70 to 0.74. Spearman correlations of estimated breeding values for each trait were 0.99. Together, these results suggest any of the three predicted methane, if used for selection, would rank animals very similarly in addition to making genetic progress in a relatively short amount of time. A genome-wide association study was also performed for each predicted methane trait. While none of the single nucleotide polymorphisms (SNP) reached the set significance threshold, an analysis of the 25 SNP nearest to the threshold showed each predicted methane trait was associated with the same genetic loci. Candidate genes found near the top 25 SNP indicate collagen related genes could be tied to predicted methane traits. Another objective of this thesis was to use a stochastic model to simulate a 100 head cow-calf operation to determine land, water, and fertilizer requirements as well as methane emissions for various regional beef production scenarios. The simulations were parameterized to replicate 74 different land regions in the Great Plains and six varying genetic potentials for mature body weight and peak lactation for cattle within those regions for a total of 444 unique scenarios. Further, the resource inputs of diets including corn products were compared to diets including grain sorghum products in regions where grains are often fed by cow-calf producers. Lastly, total herd weaning weights for each scenario were estimated based on differences in mature body weight and lactation potential. These weaning weights were used to evaluate resource use efficiency of each genetic potential. The average amount of land use for each herd was 711 hectares when corn products were used and 714 hectares when sorghum products were used. Corn-based diets required an average of 30,588,948 liters of total (irrigation and drinking) water per herd per year, while sorghum-based diets required an average of 42,776,720 liters per herd per year. There were negligible differences in fertilizer estimates between corn and sorghum-based diets (26,532 and 26,523 kilograms of nitrogen per year, respectively). The average enteric methane production for all scenarios was 8,898 and 8,925 kilograms per herd per year for corn and sorghum-based diets, respectively. In general, large, high lactation cattle had the largest environmental footprint, whereas small, low lactation cattle had the slightest. Depending on the variable evaluated, the impact of body size and lactation potential varied in importance. However, animals with a higher lactation potential required more land to grow feedstuffs regardless of size. Although heavier animals had a larger environmental impact than lighter animals with the same lactation potential for total land, blue water, fertilizer, and enteric methane production. When resource use was scaled by kilograms of weaning weight, small, high lactation animals tended to be the most efficient, provided adequate resources can be provided in a cost-effective manner to achieve their genetic potential.
Keywords: Beef cattle; Sustainability; Great Plains; Cattle genetics; Predicted methane production